Penentuan Posisi Pemain Sepak Bola Menggunakan Metode AHP dan TOPSIS - Rezza Pratama; Edy Santoso; Yuita Arum Sari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The position of the football player is very important for a player or team. Mistakes and less than optimal position of players can be a factor of defeat in a match. Therefore the positioning of players becomes a very important factor in the game of football. The purpose of this research is to assist the coach in determining the football player's position. In the Analytic Hierarcy Process (AHP) method, weighting criteria is calculated according to the importance of the criteria. Methods Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) is a method that uses distance as a reference for making comparisons. The selected alternatives are not based on criteria, but are compared with positive and negative ideal solutions. To benefit from each of these methods, feeding the authors applies a combination of AHP and TOPSIS methods. In this study, the AHP method is used for weighting. While TOPSIS method is used for alternative ranking. The data used for testing using 100 data ball players. The data is processed using AHP and TOPSIS calculations. The results of the scenario will be compared with the test data to obtain the accuracy value. From the comparison, obtained an accuracy of 58%. The result of recommendation of position according to original position of player equal to 58 data.